Review of Koutny, Stria, Farris (eds) 2021: The intercultural role of Esperanto / Interkultura rolo de Esperanto / Międzykulturowa rola esperanta - Schubert , Klaus (Investigationes Linguisticae, 2021)
Review of Ilona Koutny, Ida Stria, Michael Farris (eds) 2021: The intercultural role of Esperanto / Interkultura rolo de Esperanto / Międzykulturowa rola esperanta. (Cross-linguistic and Cross-cultural Studies 2.) Poznań: Rys, 254 pp. – https://wydawnictworys.com/the-intercultural-role-of-esperanto-interkultura-rolo-de-esperanto-miedzykulturowa-rola-esperanta-red-ilona-koutny-ida-stria-michael-farris.html